Analysis of Drug Management Process Using Lean Concept - Nuriatul Maulidiyah; Adya Hermawati; Jack Roebijoso (International Journal of Economics and Management Research, 2025)
This study aims to analyze and improve the efficiency of the drug distribution process in the IFRS pharmacy warehouse of Pasirian Regional General Hospital, Lumajang Regency, using the Lean approach. The main issues identified include a low Inventory Turnover Ratio (ITOR) of less than four times per year and the persistent occurrence of expired drugs amounting to To address these problems, Value Stream Mapping (VSM) and Future State Mapping (FSM) methods were applied to map the drug distribution process, identifying value-added (VA), non-value-added (NVA), and necessary but non-value-added (NNVA) activities. Root cause analysis using the 5 Why method revealed that the primary factors contributing to inefficiency were unscheduled drug distribution,